A submerged duckweed mutant with abundant starch accumulation for bioethanol production. Issue 12 (1st October 2020) - Liu, Yu; Xu, Hua; Wang, Yu; Tang, Xianfeng; He, Guo; Wang, Shumin; Ma, Yubin; Kong, Yingzhen; Yu, Changjiang; Zhou, Gongke
Abstract: Duckweed is one kind of promising bioenergy plant with prominent advantages such as fast growth rate and high starch content. However, almost all previous studies focused on the natural duckweed germplasms. In this study, heavy‐ion irradiation was used to establish a mutant library of Lemna aequinoctialis 6002, and one mutant named submarine‐1 ( sub‐1 ) was screened, which could accumulate more starch but with smaller granules. Unexpectedly, under proper external growth conditions such as poor nutritional status and insufficient growth space, sub‐1 mutant would sink underwater due to formation of dense tissue structure and large amount of fine starch particles with the extension of cultivation time. The starch content in the sinking sub‐1 increased to over 45% (dry weight) and was 12% higher than the floating sub‐1, highlighting that submergence can be considered as a spontaneous and efficient indicator for screening of high‐starch duckweed. Additionally, the saccharification efficiency of starch and ethanol yield had increased in sub‐1 mutant compared to the wild type. Based on the unique characteristics of sub‐1 mutant, a cultivation model of submerged duckweed in a simulated aquaculture pond was designed to get more starch‐rich biomass, enabling effective production of renewable bioenergy. Abstract : Fast growth rate and high‐efficient starch accumulation make duckweed an ideal material for bioenergy production. In order to increase the bioethanol yield, it is of great importance to screen duckweed mutants with high starch content. In this study, one mutant named submarine‐1 ( sub‐1 ) was obtained by heavy‐ion radiation mutagenesis. Compared with wild type, its starch content doubled, and its biomass of single plant and biomass unit area increased by 13.5% and 74% respectively. Surprisingly, we found that sub‐1 could sink under certain conditions, and the starch content of sinking sub‐1 increased by 12% compared with the floating sub1 . Additionally, the starch saccharification efficiency and ethanol yield had increased compared to wild type. Therefore, we believe sub‐1 is an ideal engineering duckweed for bioenergy production.